An international cohort study of autosomal dominant tubulointerstitial kidney disease due to REN mutations identifies distinct clinical subtypes - Živná, Martina; Kidd, Kendrah; Zaidan, Mohamad; Vyleťal, Petr; Barešová, Veronika; Hodaňová, Kateřina; Sovová, Jana; Hartmannová, Hana; Votruba, Miroslav; Trešlová, Helena; Jedličková, Ivana; Sikora, Jakub; et al. (Kidney international, 2020)
There have been few clinical or scientific reports of autosomal dominant tubulointerstitial kidney disease due to REN mutations (ADTKD-REN), limiting characterization. To further study this, we formed an international cohort characterizing 111 individuals from 30 families with both clinical and laboratory findings. Sixty-nine individuals had a REN mutation in the signal peptide region (signal group), 27 in the prosegment (prosegment group), and 15 in the mature renin peptide (mature group). Signal group patients were most severely affected, presenting at a mean age of 19.7 years, with the prosegment group presenting at 22.4 years, and the mature group at 37 years. Anemia was present in childhood in 91% in the signal group, 69% prosegment, and none of the mature group. REN signal peptide mutations reduced hydrophobicity of the signal peptide, which is necessary for recognition and translocation across the endoplasmic reticulum, leading to aberrant delivery of preprorenin into the cytoplasm. REN mutations in the prosegment led to deposition of prorenin and renin in the endoplasmic reticulum-Golgi intermediate compartment and decreased prorenin secretion. Mutations in mature renin led to deposition of the mutant prorenin in the endoplasmic reticulum, similar to patients with ADTKD-UMOD, with a rate of progression to end stage kidney disease (63.6 years) that was significantly slower vs. the signal (53.1 years) and prosegment groups (50.8 years) (significant hazard ratio 0.367). Thus, clinical and laboratory studies revealed subtypes of ADTKD-REN that are pathophysiologically, diagnostically, and clinically distinct.
Keywords: Young Adult; signal peptide; Male; kohortové studie; mutace; characterization; mladý dospělý; Cohort Studies; Child; prosegment; Anemia; polycystická choroba ledvin; dítě; Adult; dospělí; autosomal dominant tubulointerstitial kidney disease; mužské pohlaví; mutation; lidé; ženské pohlaví; Renin; Humans; anemie; Mutation; Female; Polycystic Kidney Diseases; renin